A Correlation Between Fractional Anisotropy Variations and Clinical Recovery in Spinal Cord Infarctions. Issue 2 (30th December 2011) - Théaudin, Marie; Saliou, Guillaume; Denier, Christian; Adams, David; Ducreux, Denis
<x xml:space="preserve">Abstract</x> ABSTRACT PURPOSE To describe diffusion‐weighted imaging and diffusion tensor imaging variations in spinal cord infarctions. METHODS We studied the apparent diffusion coefficient (ADC) and fractional anisotropy (FA) local variations in 2 patients with spinal cord infarcts in the conus region at days 3–4, 9–10, and 15–22 after clinical onset, and correlated them with the clinical outcome. RESULTS Both patients (19 and 53 years‐old) presented spinal cord infarction unraveled by paraparesis and bladder dysfunction. Although initial clinical and radiological presentations were similar, the first patient early and fully recovered whereas the second kept severe bladder dysfunctions. Early absolute values of FA and ADC did not seem to correlate with outcome. At day 9–10, the second patient, who presented definitive sequel, had decreasing values of FA in the ischemic region whereas they had increased in the first patient, who fully recovered. CONCLUSION FA values could be an interesting prognosis marker in spinal cord ischemia, which needs to be confirmed by a larger study.